Self Efficacy terhadap Kecemasan dalam Praktek Penyuluhan Kesehatan Di Lahan Praktek Mahasiswa - Usman Seri (Jurnal Vokasi Kesehatan, 2016)
Abstract: Self Efficacy Against Anxiety in Practice Health Education Students In Land Practices. The objective is to find the relationship of self-efficacy against anxiety students when providing health education in schools. This study uses the analytic method with cross-sectional approach. The experiment was conducted at the Department of Nursing Polytechnic Pontianak. The research was conducted for 6 (six) months from April 2015 to September 2015. The research subject that all students / I Prodi DIV Nursing Programs Singkawang 2015 that amounted to 52 (total sample). The results showed the analysis of the relationship between self-efficacy with anxiety found that as many as 17 (37%) of students experiencing mild anxiety, 27 (58.7%) of students who experienced moderate anxiety and 2 (4.3%) experienced severe anxiety with positive self-efficacy, While 2 (4.3%) students experiencing mild anxiety with negative self-efficacy.Abstrak : Self Efficacy Terhadap Kecemasan Dalam Praktek Penyuluhan Kesehatan Di Lahan Praktek Mahasiswa. Tujuan penelitian yaitu untuk mencari hubungan self efficacy terhadap kecemasan mahasiswa saat memberikan penyuluhan kesehatan di sekolah. Penelitian ini menggunakan metode analitik dengan pendekatan Cross sectional. Penelitian dilaksanakan di Jurusan Keperawatan Poltekkes Pontianak selama 6 (enam) bulan dari bulan April hingga September 2015. Subjek Penelitian yaitu Semua mahasiswa/i Prodi D-IV Jurusan Keperawatan Singkawang tahun 2015 yang berjumlah 52 orang (total sampel). HasilÂ  penelitian menunjukkan analisis hubungan antara self efficacy dengan kecemasan diperoleh sebanyak 17 (37%) mahasiswa mengalami kecemasan ringan, 27 (58,7%) mahasiswa yang mengalami kecemasan sedang dan 2 (4,3%) orang mengalami kecemasan berat dengan self efficacy positif. Sedangkan 2 orang (4,3%) mahasiswa mengalami kecemasan ringan dengan self efficacy negatif.